Nilai tambah pada pengolahan ikan tuna beku di PT. Kelola Mina Laut Pelabuhan Perikanan Samudera Kendari - Septiyanti, Feni; Yusuf, Sarini; Huli, La Ode; Budiyanto; Riani, Irdam; Sriwulan, Desy (Jurnal Sosial Ekonomi Perikanan, 2023)
Tuna is one of the important economical fishery commodities exported in frozen form. One of the companies that develops a frozen tuna processing business in Kendari City is the company PT. Manage Mina Laut Kendari Ocean Fishing Port This study aims to analyze how much added value pt. Manage Mina Laut in March 2022. This research uses the case study method with data collection through interviews, observations, documentation, and literature studies. Interviews wre conducted to respondents consisting of one company manager and 3 representatives of each employee division and one supervisor of PT Kelola Mina Laut. The analysis used is a quantitative analysis, namely the added value obtained is calculated using the formula NTP (Product Added Value) = NP – Na (NTP = Product Added Value, NP = Product Value, and Na = Intermediate Cost Value). Production in this study was calculated for 26 times a month as carried out by the company. The results showed that the average added value of the product was IDR 28,939,353/production with a value-added ratio of 26.91% for each production cycle. The added value obtained by PT. Kelola Mina Laut at PPS Kendari was low. It is necessary to increase the amount of production with careful consideration on raw materials and packaging. The high price of raw materials and plastic packaging contributes to the suboptimal added value